PT. Gudang Garam Profitability Analysis on The Indonesia Stock Exchange - Atriani, Windi; Ali, Muhammad; Nohong, Mursalim (Economics and Business Journal (ECBIS), 2023)
This study aims to determine the financial performance of PT. Gudang Garam Tbk in terms of profitability ratio analysis for 2019-2022. The type of research used is descriptive quantitative. The data collection technique in this study uses documentation techniques in the form of balance sheets and income statements for 2018-2022. The profitability ratios used in this study include Gross Profit Margin (GPM), Net Profit Margin (NPM), Return on Assets (ROA), Return on Equity (ROE), and Earnings Per Share (EPS). The results showed that the financial performance of PT. Gudang Garam Tbk for the last four years has tended to be unfavorable, because the average value of the profitability ratio is below the expected standard of measurement. To overcome the problem of declining financial performance, PT. Gudang Garam Tbk must identify and control production and distribution costs more efficiently, develop appropriate pricing and sales strategies, manage accounts receivable properly, and be prudent in using loans with favorable interest rates to increase the company's net profit.